Deradicalization of Religion Through Pluralism Education Methods in Jembrana Bali - Made Saihu (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
Deradicalization through education is one of the main agendas in counteracting the massive spread of radicalism in Indonesia. This study aims to describe the effectiveness of the religious pluralism education method from the perspective of